The Role of International Organizations in the Protection of Oil Resources in Times of Armed Conflict - Mohammed Mesha, Researcher. Nada; Nazem Saadoun Al-Abadi, Assist.Prof.Dr. Osameh (Basra studies journal, 2025)
International mechanisms for the protection of petroleum resources during armed conflicts are of great importance, especially given the increasing prevalence of both international and non-international armed conflicts and the intensified use of weapons. Today, the international and humanitarian landscape is in urgent need of strengthened regulatory and legal frameworks to address the serious violations committed against oil resources. Therefore, it is essential to support and empower the international organizations involved in this field, enhancing their role in regions experiencing armed conflict. The research concludes that current international mechanisms do not provide sufficient protection for petroleum resources. Despite the existence of several agreements that make reference to this issue, their impact remains limited due to political considerations that undermine their effectiveness.